The effect of nicotine and dextrose on endoplasmic reticulum stress in human coronary artery endothelial cells - Gonzales, Krista (Toxicol Res (Camb), 2021)
Cigarette smoking is one of the major causes of coronary artery disease (CAD) as is diabetes. However, nicotine has been generally regarded as safe and is used in smoking cessation programs. This presumption of nicotine safety was examined in human coronary artery endothelial cells (HCAEC). Endoplasmic reticulum (ER) stress was measured using the secreted alkaline phosphatase (SAP) assay. The ER stress markers inositol-requiring enzyme 1α (IRE1α), phospho-IRE1α, double-stranded RNA-activated protein kinase-like endoplasmic reticulum kinase (PERK), phospho-PERK, activating transcription factor 6 (ATF6), and glucose-related protein 78 (GRP78) were measured by western blot. Cell viability was measured using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and crystal violet staining. Intact and cleaved caspase 3, BH3 interacting-domain death agonist (BID), and B-cell lymphoma 2 (Bcl2) were measured by western blot. In cells transfected with the SAP expression plasmid, treatment with nicotine resulted in a dose-dependent decrease in SAP expression with no noticeable toxicity. Nicotine (10 nM) also increased IRE1α and PERK phosphorylation, and ATF6 and GRP78 expression. Although nicotine at concentrations up to 10 μM did not cause cell death, treatment of HCAEC with 10 nM nicotine in the presence of 13.8 mM dextrose aggravated ER stress, increased cell death, increased cleaved caspase 3 and BID, and decreased BCL2. Nicotine at concentrations commonly achieved in nicotine-replacement therapy (NRT) significantly increased ER stress in HCAEC and aggravated dextrose-induced ER stress and cell apoptosis. People using electronic cigarettes and on NRT may be at increased risk for CAD.